PENINGKATAN KEMAMPUAN BERBICARA SISWA DENGAN METODE DEMONSTRASI KELAS V SDN 02 SUNGAI BETUNG - Santoso, Santoso; Syamsiati, Syamsiati; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is to improve students' speaking ability by using class V demonstration method of State Elementary School 02 Betung River, Bengkayang Regency. The method used is descriptive method with class action research form. The study was conducted in three cycles and each cycle consisted of one meeting with a time allocation of 3 x 35 minutes. The results of the teacher's ability to plan lessons from cycle I with an average score of 3.48 to 3.70 in cycle II to 3.81 in cycle III and can be categorized very well. The result of teacher ability in conducting learning from the average value of cycle I 3.41 to 3.66 in cycle II, to 3.87 in cycle III and can be categorized very well. Improving students' speaking ability by using class V demonstration method is evidenced by the average achievement of students in the first cycle of 77.77, in the second cycle of 82.14 and in the third cycle of 84.52. Based on this data analysis, it can be concluded that the demonstration method can be used to improve the speaking ability of grade V students of Secondary School 02 Sungai Betung, Bengkayang Regency.Â Keywords: Speaking skills, Demonstration methods